In vitro anthelmintic activity of papaya leaves (Carica papaya) chloroform extract against the third-stage larvae of strongyles from sheep - Ahmad Pauzi, Aisyah (2016)
Parasitic gastroenteritis (PGE) is one of the major causes of economic losses in small ruminant practices. Helminthiasis has been reported to cause severe morbidity and mortality annually in the small ruminant industry in Malaysia, whereby chemical anthelmintic has been used for treatment and prevention. However, frequent and indiscriminate use of chemical anthelmintic has resulted in resistance problem in the small ruminant population. This study aimed to evaluate the anthelmintic effect of papaya leaves (Carica papaya) chloroform extract (CPE) on the third-stage larvae (L3) of strongyles from sheep. The L3 larvae of strongyles from sheep were harvested 7 days post faecal culture technique. Six petri dishes containing one hundred L3 per perti dish were used for each of the CPE treatment groups, one Levamisole and one negative control group. The mortality rate of these larvae was observed at 2, 4, 6, 24 and 48h. Results showed that CPE at the concentrations of 7.5, 10.0 and 12.5 mg/ml, exerted significant anthelmintic activity against L3 with a mortality rate up to 99% (KW=115.559, df= 4, p <0.05). Levamisole (10mg/ml) induced 100% L3 mortality at the second hour of observation. In conclusion, CPE could potentially be used as an alternative herbal anthelmintic agent in the future. However, further in vivo research is needed to determine the anthelmintic effect of CPE in sheep.